AB0185 Endothelin-1 stimulates the profibrotic alternative activated phenotype in cultured human macrophages isolated from systemic sclerosis patients. (15th June 2017) - Soldano, S; Montagna, P; Brizzolara, R; Trombetta, AC; Corallo, C; Pizzorni, C; Paolino, S; Sulli, A; Ghio, M; Smith, V; Giordano, N; Cutolo, M
Abstract : Background: In the damaged tissue of systemic sclerosis (SSc) patients, the presence of immune inflammatory infiltrate, characterized by T-cells and macrophages, represents an important early pathological event in the fibrotic process (1). In the macrophage population, the alternatively activated (M2) macrophages were observed in both peripheral blood and damage tissues of SSc patients and they participate in the fibrotic process exerting profibrotic effects, primarily by the production and release of transforming growth factor β1 (TGFβ1) (1, 2). These cells are characterized by the expression of specific phenotype markers, such as mannose receptor (CD206) and scavenger receptors (CD204 and CD163), and the production of specific chemokines (i.e. macrophage derived chemokine, CCL-22) (3). Endothelin-1 (ET1) plays an important role in the fibrotic process of SSc by inducing the profibrotic phenotype in endothelial cells and fibroblasts (4). Objectives: To evaluate the ability of ET1 to upregulate the profibrotic gene expression profile characterizing the M2 macrophages in cultured monocytes/macrophages isolated from SSc patients. Methods: Human monocytes were isolated from peripheral blood mononuclear cells of 4 SSc patients (mean age 59±11years, 2 females and 2 males, treated with vasodilator drugs) using a monocyte isolation kit. Cultured cells were maintained in RPMI growth medium for 24hrs and then treated with ET1 (100nM) for 6 days or treated for 1hr with ET receptor antagonist (ETA/B RA, bosentan 10μM) before stimulation with ET1. Cultured cells maintained in RPMI growth medium were used as untreated cells. Gene and protein expression of M2 phenotype markers and TGFβ1 were evaluated by quantitative real-time polymerase chain reaction (qRT-PCR) and Western blotting (WB). Statistical analysis was carried out using a Mann-Whitney non-parametric test. Results: In cultured SSc macrophages, ET1 induced the upregulation of the gene expression of CD206, CD204, CD163, and CCL22 compared to untreated cells. Moreover, ET1 increased the TGFβ1 gene expression compared to untreated cells. ETA/B RA partially contrasted the gene expression of CD204 and CD206. However, ETA/B RA antagonized the ET1-mediated increase in the gene expression of CD163, CCL22 and TGFβ1. WB confirmed the results obtained by qRT-PCR. Conclusions: Preliminary results showed the ability of ET1 to stimulate a profibrotic M2 phenotype in cultured human SSc macrophages characterized by the overexpression of TGFβ1, and this process is partially contrasted by the action of ETA/B RA. References: Higashi-Kuwata N et al. Arthrit Res Ther. 2010;12:R128. Stifano G et al. Curr Rheumatol Rep. 2016;18:2. Wynn TA et al. Nat Rev. 2013;496:445–55. Cipriani P et al. J Rheumatol. 2015;42:1808–16. Disclosure of Interest: None declared